1990
DOI: 10.1002/1097-0142(19900101)65:1<53::aid-cncr2820650112>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the uterine cervix

Abstract: In Finland, the incidence of cervical cancer has shown a decreasing tendency since the 1960s. The same trend, however, has not been noticed in the incidence of cervical adenocarcinoma. The reason for this is not known, although many studies have shown differences in the cause, epidemiology, and biology of the epidermoid and adenocarcinoma of the uterine cervix. A total of 106 new patients with cervical adenocarcinoma were treated at our institution from 1976 to 1980, which represents 20.4% of all cervical carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 15 publications
3
34
1
1
Order By: Relevance
“…Temporal misclassification between adenocarcinoma and squamous cell carcinoma could have occurred, but it is unlikely that this had had an important impact on trends. Better histological specification of cervical cancer over time has been documented (Kjaer and Brinton, 1993;Leminen et al, 1990) and, although this could also have increased the number of squamous cell carcinomas, the impact on the reported incidence rates of adenocarcinomas should be greater because of the smaller number of cases. It remains difficult to explain why this effect, if important, would be confined to younger women in recent birth cohorts.…”
Section: Strengths and Caveats In The Interpretation Of Cervical Cancsupporting
confidence: 64%
“…Temporal misclassification between adenocarcinoma and squamous cell carcinoma could have occurred, but it is unlikely that this had had an important impact on trends. Better histological specification of cervical cancer over time has been documented (Kjaer and Brinton, 1993;Leminen et al, 1990) and, although this could also have increased the number of squamous cell carcinomas, the impact on the reported incidence rates of adenocarcinomas should be greater because of the smaller number of cases. It remains difficult to explain why this effect, if important, would be confined to younger women in recent birth cohorts.…”
Section: Strengths and Caveats In The Interpretation Of Cervical Cancsupporting
confidence: 64%
“…First described by Friedell in 1953 [7] and subsequently shown to have a propensity for late recurrence and the development of invasive adenocarcinoma [22], ACIS represents approximately 9-25% of adenocarcinomas of the cervix [5,14], which account for 8-26% of cervical carcinomas [11,20,21]. Patients with ACIS have a similar epidemiologic profile to those with invasive adenocarcinoma of the endocervix [3,4,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that over the past three decades, SCC of the cervix has been progressively decreasing in proportion to the increase of adenocarcinoma, also found in our study [13][14][15][16][17]. However, in a more current reality, this can be explained due to the better public access to the examination of cervical cytological screen- ing.…”
Section: Discussionmentioning
confidence: 99%